The Influence of Social Media Language on Generation Z Identity in Indonesia - Anita Febiana Putri; Bunga Malika Putri; Erningsih Putri Suparman; Wulan Astriani; Nargis Nargis (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study explores the impact of social media language on identity formation among Generation Z in Indonesia, a demographic that has grown up in a digital landscape characterized by extensive online interactions. With approximately 202 million internet users in Indonesia as of 2023, social media platforms such as Instagram, TikTok, and Twitter have become vital arenas for self-expression and cultural dialogue. The research employs a qualitative approach, utilizing semi-structured interviews, focus group discussions, and online observations to gather rich, contextual data from urban youth. Findings reveal that the dynamic linguistic landscape of social media—marked by the use of slang, memes, and code-switching—plays a crucial role in shaping personal and collective identities. Additionally, the study highlights the influence of local and global cultural trends, as well as the role of social media influencers in shaping youth perceptions of identity. The implications of these findings extend to educators, policymakers, and mental health professionals, emphasizing the need for a nuanced understanding of the challenges and opportunities presented by social media in the identity formation process.